PEMBERDAYAAN MASYARAKAT UNTUK PENCEGAHAN PENYEBARAN TUBERKULOSIS DI DESA TANIMULYA KECAMATAN NGAMPRAH KABUPATEN BANDUNG BARAT DENGAN MENERAPKAN TEKNOLOGI PEMBUATAN HANDSANITIZER BERBAHAN DASAR DAUN SELEDRI (Apium graveolens L.) - Marliana, Nina; Kurniati, Iis; Abror, Yogi Khoirul; Patria, Cecep (Poltekkes Kemenkes Bandung, 2025)
TB remains a global problem. In our country, TB prevention, including thorough handwashing, is a fairly effective health protocol for preventing TB transmission. Hand sanitizer is an alcohol-based hand cleaning liquid used to reduce contaminating bacteria by up to 99.9% by using it without rinsing with water. This liquid contains various ingredients that very quickly kill bacteria on the skin of the hands. Hand sanitizer aims to remove dirt and flora that stick to our hands. Celery (A. graveolens L.) is a type of vegetable plant with a menthol and distinctive celery aroma. Usually, celery is only used as a complementary ingredient in food preparations, but it turns out that celery contains several beneficial compounds such as flavonoids, saponins, tannins, essential oils as antibacterials. Therefore, celery can be used as a hand sanitizer. The practical goal of this PPDM is for the community in Tanimulya Village, Ngamprah District, West Bandung Regency to process celery for use as a hand sanitizer. The method offered is technology transfer through counseling, training, and mentoring. The target of the PPDM program was Tani Mulya Village in West Bandung Regency, given the dense population and high pollution in the area, necessitating hand sanitizer to prevent the spread of tuberculosis through the hands. The results of the PPDM program in Tani Mulya Village showed an increase in community knowledge and skills, as evidenced by the pre- and post-test results. The average pre-test score was 66.2, while the post-test score increased to 75.7.